2014
DOI: 10.1007/s00441-014-2029-z
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and gap junctions in the inner ear – it’s not just about K+ recycling

Abstract: Normal development, function and repair of the sensory epithelia in the inner ear are all dependent on gap junctional intercellular communication. Mutations in the connexin genes GJB2 and GJB6 (encoding CX26 and CX30) result in syndromic and non-syndromic deafness via various mechanisms. Clinical vestibular defects, however, are harder to connect with connexin dysfunction. Cx26 and Cx30 proteins are widely expressed in the epithelial and connective tissues of the cochlea, where they may form homomeric or heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 109 publications
1
87
0
Order By: Relevance
“…Classically, the connexin-based gap junction network in the adult cochlea is thought to contribute to cochlear homeostasis (Zdebik et al, 2009). Mouse models confirmed that Cx26 and Cx30 are involved in a wide range of activities important for the normal function of the developing and mature hearing system (Mammano, 2013; Jagger and Forge, 2015; Kelly et al, 2015; Wingard and Zhao, 2015; Zhu et al, 2015). …”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Classically, the connexin-based gap junction network in the adult cochlea is thought to contribute to cochlear homeostasis (Zdebik et al, 2009). Mouse models confirmed that Cx26 and Cx30 are involved in a wide range of activities important for the normal function of the developing and mature hearing system (Mammano, 2013; Jagger and Forge, 2015; Kelly et al, 2015; Wingard and Zhao, 2015; Zhu et al, 2015). …”
Section: Introductionmentioning
confidence: 83%
“…Cx26 and Cx30 are the predominant connexins in the mammalian cochlea and the only isoforms expressed in the sensory epithelium (Jagger and Forge, 2015; Wingard and Zhao, 2015). These connexins have been shown to form extrajunctional hemichannels (Anselmi et al, 2008; Majumder et al, 2010) and also to coassemble to form homomeric or heteromeric gap junction channels between nonsensory cells (Forge et al, 2003; Martínez et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the inner ear, these large Cx30 gap junction plaques are found between supporting cells within the avascular organ of Corti (Sun et al, 2005;Jagger and Forge, 2006), which plays a key role in K + buffering and metabolite transfer (Jagger and Forge, 2014). Therefore, large gap junction plaques may be crucial for maintaining homeostasis by maximizing cell-cell transfer of metabolites and nutrients (Chang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mutations in GJB6 encoding Cx30 can also result in hearing impairment. Jagger and Forge (2015) argue that, whereas evidence exists that the gap junctions in the cochlea composed of these two connexins provide a pathway for direct cell to cell passage of K + ions to maintain the ionic environment necessary for sound perception and sensory cell survival, channels of almost any composition could allow K + transfer. Thus, the authors suggest that other connexin/gap junction roles might be affected by GJB2 or GJB6 mutation.…”
mentioning
confidence: 99%